2011
DOI: 10.1158/1055-9965.epi-11-0136
|View full text |Cite
|
Sign up to set email alerts
|

Age-Period-Cohort Analysis of Primary Bone Cancer Incidence Rates in the United States (1976–2005)

Abstract: Background: Primary bone cancer comprises three major histologic types: osteosarcoma (OS), Ewing sarcoma (ES), and chondrosarcoma (CS). Given the limited knowledge about the etiology of primary bone cancer, we undertook an age-period-cohort (APC) analysis to determine whether incidence varied by birth cohort or calendar period. The purpose was to examine the temporal development of each bone cancer type and generate etiologic hypotheses via the observed birth cohort-related changes.Methods: An APC model was fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 37 publications
6
48
0
1
Order By: Relevance
“…It was originally reported that males were affected with osteosarcoma more frequently than females 1, 15, 16, 17. However, recent reports suggested that the osteosarcoma incidence may be equal in both sexes 18, 19. This finding was consistent with our study that the males shared the similar incidence with the females in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally reported that males were affected with osteosarcoma more frequently than females 1, 15, 16, 17. However, recent reports suggested that the osteosarcoma incidence may be equal in both sexes 18, 19. This finding was consistent with our study that the males shared the similar incidence with the females in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…It may thus be postulated that a low incidence of Paget disease (e.g., in Japan) [36] combined with better cancer treatment over the past decades (thereby reducing late effects due to chemotherapy and radiotherapy) may have been important factors in lower incidence of OS later in life [4]. Anfinsen et al [32] have reported age-period-cohort analysis of US data for bone cancers where a decline in incidence rates of OS in the USA during 1976-2005 among those over 60 years (cohorts born during 1905-1934) was seen. This observation, representing the second peak of the bimodal age-incidence curve of OS and a peak incidence around 70 years of age, can be extended to the UK in both sexes, but in this analysis, such a trend was not evident among US women.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, estrogen has been shown to stimulate vascular endothelial growth factor, which is a characteristic trait of progression of CS [16]. Anfinsen et al [32] have reported an increase in incidence rates of CS among females in the USA during 1976-2005 (although no change in incidence among men was seen). The declining cohort trends among US women born during 1935-1975 are replicated for UK women in this study, corresponding to the introduction of exogenous estrogen exposures (oral contraceptives, hormone therapy) in the 1960s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 10 percent of children with cancer are diagnosed with sarcomas, compared to 8 percent for young adults and 1 percent of adults (>40yrs old) diagnosed with cancer. Ewing sarcoma, osteosarcoma and rhabdomyosarcoma constitute about three quarters of all children with sarcomas whereas liposarcoma, leiomyosarcoma, undifferentiated sarcomas, synovial sarcoma and MPNST represent some of the more common histologies in the adult population (32, 33). Localized sarcomas are frequently treated with multimodal therapy including surgery, radiation therapy and anthracycline based chemotherapy with curative intent.…”
Section: Discussionmentioning
confidence: 99%